2000
DOI: 10.1021/om0002475
|View full text |Cite
|
Sign up to set email alerts
|

Alternative η5- and η6-Bonding Modes for Bis(fluorenyl)lanthanide Complexes by Reactions with AlR3 and Succesive Addition of THF

Abstract: Reversible and equilibrium isomerization of η 5 -bis(Me 3 Si-fluorenyl)-rare earth metal complexes to η 6 -bis(Me 3 Si-fluorene-AlR 3 )-rare earth metal complexes, which is a novel type of metallotropic tautomerism, was realized by the addition of AlR 3 to the former complexes. Resulting η 6 -complexes also changed to the initial η 5 -complexes reversibly by the addition of excess THF. η 5 -Bis(Me 3 Si-fluorenyl)Sm(THF) 2 (1) was prepared by reaction of Me 3 Sifluorenylpotassium with SmI 2 (THF) 2 , and its st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 26 publications
1
50
1
4
Order By: Relevance
“…6 Previous attempts to prepare mono-fluorenyl lanthanide complexes by the 1 : 1 reaction of (fluorenyl)Li and LnCl 3 have been unsuccessful. 2,3 Here, we report the X-ray crystal structures of (η 5 -fluorenyl)LnI 2 (py) 3 (Ln = La (1), Nd (2)), which are the first examples of neutral, mono-fluorenyl complexes of the lanthanides.…”
Section: -7mentioning
confidence: 99%
“…6 Previous attempts to prepare mono-fluorenyl lanthanide complexes by the 1 : 1 reaction of (fluorenyl)Li and LnCl 3 have been unsuccessful. 2,3 Here, we report the X-ray crystal structures of (η 5 -fluorenyl)LnI 2 (py) 3 (Ln = La (1), Nd (2)), which are the first examples of neutral, mono-fluorenyl complexes of the lanthanides.…”
Section: -7mentioning
confidence: 99%
“…[6][7][8] One of the simple and most effective synthetic routes to mono(arene)-lanthanide complexes, containing arene ligands that are coordinated to the metal in the η 6 mode, is the reaction of a lanthanide halide with aluminium(III) halides in an arene solution. Employing this method, a series of mononuclear complexes of Sm, [3,[9][10][11] La, [6] Nd, [6,10] Gd, [10] Yb, [10] Y, [16] Pr, [16] Eu, [17] and U [3,15] was prepared. Benzene and its alkylated derivatives have been used as the arene ligands.…”
Section: Introductionmentioning
confidence: 99%
“…(10)°in compound 4, but smaller than that of 79.26 (18)°found in (C 13 H 9 ) 2 Yb(THF) 2 [10]. This angle is smaller than the O-Yb-O angle of 84.5(3)°and 86.3(3)°found in [g 5 :g 1 -(CH 3 OCH 2 CH 2 C 9 H 5 SiMe 3 )] 2 Yb II [11b], 83.1 (14)°found in [g 5 :g 1 -(C 4 H 7 OCH 2 C 9 H 5 SiMe 3 )] 2 Yb II [11g], also smaller than the N-Yb-N angle of 92.8(5)°, 103.7(2)°found in [g 5 :g 1 -(Me 2 NCH 2 CH 2 -C 9 H 5 SiMe 3 )] 2 Eu II and [g 5 :g 1 -(Me 2 NCH 2 CH 2 C 9 H 6 )] 2 Yb II [11c], but larger than the corresponding angles of 68.05(12)°found in (C 13 H 9 ) (C 5 Me 5 )Yb(DME) [10], and the O-Eu-O angle of 75.15(10)°in compound 4 is smaller than the N-Eu-N angle of 94.49(15)°f ound in compound 6, respectively, suggesting steric and electronic effects.…”
Section: Resultsmentioning
confidence: 92%
“…(C 13 H 9 ) 2 Sm(THF) 2 [19b], [(C 5 Me 5 )Sm(OAr)] 2 [20], (9-Me 3 Si-C 13 H 8 ) 2 -Sm(THF) 2 , (9-Me 3 Si-C 13 H 8 ) 2 Yb(THF) 2 [21]. Examination of the solvents effects on the catalytic activities of the catalysts 3-6 indicated that the catalytic activities of the catalysts have good activity in toluene and THF.…”
Section: Ring-opening Polymerization Of E-caprolactonementioning
confidence: 99%
See 1 more Smart Citation